2012 Sixth International Conference on Research Challenges in Information Science (RCIS) 2012
DOI: 10.1109/rcis.2012.6240445
|View full text |Cite
|
Sign up to set email alerts
|

Interoperability for model-driven development: Current state and future challenges

Abstract: Nowadays, the emergence of several model-driven development (MDD) proposals that are related to multiple domains requires the definition of proper interoperability mechanisms that facilitate the reuse of knowledge in the MDD community by taking advantage of already defined modeling languages, tools, and standards. However, there are no recent studies that cover the existent interoperability alternatives in the model-driven domain nor is there a common interoperability framework. This paper confronts this situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Nine secondary studies explicitly assess the quality of the primary studies they include. Eight of those secondary studies use an ad hoc assessment, with custom-made criteria tailored for the specific domain those reviews are covering (Delgado et al 2013;Domínguez et al 2012;Giachetti et al 2012;Giraldo et al 2014;Hansson et al 2014;Misbhauddin and Alshayeb 2015;Mohagheghi and Dehlen 2008;Santiago et al 2012). Neto et al (2014) used guidelines (Kitchenham and Charters 2007) for the quality assessment of the included primary studies.…”
Section: Quality Evaluation Of Secondary Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine secondary studies explicitly assess the quality of the primary studies they include. Eight of those secondary studies use an ad hoc assessment, with custom-made criteria tailored for the specific domain those reviews are covering (Delgado et al 2013;Domínguez et al 2012;Giachetti et al 2012;Giraldo et al 2014;Hansson et al 2014;Misbhauddin and Alshayeb 2015;Mohagheghi and Dehlen 2008;Santiago et al 2012). Neto et al (2014) used guidelines (Kitchenham and Charters 2007) for the quality assessment of the included primary studies.…”
Section: Quality Evaluation Of Secondary Studiesmentioning
confidence: 99%
“…Giachetti et al (2012) surveyed this research area and found that although this was a hot topic, it was common to find several different approaches tackling Software Qual J essentially the same issues, but not relating them, particularly when it came to interoperability approaches focusing on supporting MDD processes. The authors found challenges in reaching a consensus in terminology and concepts used, which is a crucial step toward the desired interoperability.…”
Section: Summary Of Secondary Studies Contributionsmentioning
confidence: 99%
“…For the transformation of goal models to business process models, we use the GoBIS technique [6]. GoBIS uses FRISCO [24] as a pivot ontology [39] to ensure ontological consistency among models. Its main construct is that the satisfaction of a dependency between actors involves a communicative interaction between these actors.…”
Section: B Analysis Objectmentioning
confidence: 99%
“…For this purpose, the concept of verification measure is defined, which has been introduced and explained in [44]. The need for counting with verification mechanisms for the execution of interoperability operations is founded on the systematic review presented in [53], where the lack of approaches for performing this kind of verification is clearly indicated.…”
Section: Verification Approach For Aligning Goal-oriented Modeling and Mdd Processesmentioning
confidence: 99%